Interactive, computer-based, and situated design for innovative formative assessment approaches - Federica Morleo; Pasquale Anselmi; Alessandra Vitanza (PLoS ONE, 2025)
Social and teamwork skills are essential for today’s teachers, yet their assessment in authentic contexts is challenging. This study presents the design, development and validation of an innovative computer-based test, designed to assess collaborative and teamwork skills in preprimary and primary school teachers and referred to as the ‘CoTeSt’ (Collaborative and Teamwork Skill test). Based on Situated Action Theory, the test immerses participants in realistic team interactions using conversational agents within a narrative framework. Teachers are asked to solve problems, collaborate with virtual colleagues, and provide feedback. The test consists of 20 dichotomously scored items in both multiple-choice and short answer, and it was administered to 139 Italian teachers. Test validation involved qualitative and quantitative methods, confirming that the items actually assess the skills they were assumed to evaluate. Post-test interviews and group discussions highlighted the tool’s user-friendly design and its potential to foster self-reflection, professional dialogue, and continuous skill development. The CoTeSt represents a meaningful step toward empowering teachers with critical social skills and fostering a culture of collaboration and growth in education.